Heterogeneous Catalysis Mechanism - Jin, Jia-Min (European Journal of Applied Sciences, 2022)
In this paper, two heterogeneous catalysis mechanisms are introduced, namely: Chemical Reaction Mode Cyclic Catalysis Mechanism-CRM and Electron Cyclic Donate-Accept Catalysis Mechanism-ECDAM or Electron Orbital Deformation-Recovery Cyclic Catalysis Mechanism -EODRM . Some difficulties encountered by CRM are listed. The author clearly points out that the CRM is not credible。This false theory has misled us for more than 100 years。 About ECDAM, the article also gives a brief description. The main point of ECDAM is that the catalysis phenomenon are physical rather than chemical phenomenon. The catalysts do not participate in chemical reactions, It’s just contact，electron cyclic donate-accept or electron orbital deformation-recovery cycle.. The theory contains three viewpoints: 1, There is a boundary between the catalyst and the poison. 2, The active of the catalyst or the degree of toxicity of the poison is closely related to the electronegative value of the catalyst or poison. 3, The active of catalyst is closely related to the chemical state of the catalyst.. The selectivity of catalyst is also related to electronegative or energy level. According to ECDAM, The author considers that there are several problems worth studying in production and scientific research. such as: alumina is a poison in the Fe ammonia synthesis catalyst. The Cordierite (2MgO·2Al2O3·5SiO2 ) ceramic honeycomb support is also a poison in automotive exhaust purification catalyst .The Cordierite ceramic honeycomb is retardant in wall flow filter for diesel vehicles. Activated carbon is a poison in the Ruthenium catalyst for ammonia synthesis. Alumina and activated carbon all are a poison to noble metal catalysts, and so on.